WRITTEN MATHEMATIC COMMUNICATION ABILITY DESCRIPTION ON MATHEMATICS LEARNING FOR CLASS VIII STUDENT SMPN 8 PAREPARE - Ainun Dwi Cahyani; Muhammad Ahsan; Buhaerah (Jurnal Prinsip Pendidikan Matematika, 2022)
This study aims to produce a description of the written mathematical communication skills of SMP class VIII students on the subject matter of patterns and number sequences. The research method used by the researcher is descriptive qualitative research. Sources of data are taken from primary data and secondary data. Data collection techniques consist of observation, interviews, and documentation. The data obtained by the researcher was analyzed using analytical methods with the steps of data reduction, data presentation, and conclusions and verification. Based on the study results, the written mathematical communication skills of class VIII students at SMPN 8 Parepare, the subject matter of patterns and number sequences, seen from the four indicators, were classified as average. This is evidenced by the results of the data presentation of indicators where indicators 3 and 4 are combined as follows: 1). Presenting and rewriting the description of a given picture or pattern using their written language is considered not good; 2). Declaring the picture into a mathematical model and completing it is considered good; 3). Declaring mathematical situations or everyday events into mathematical models in writing and connecting mathematical ideas with relevant images and solving them is considered good.